Conjugated lineolic acid and insulin sensitivity : insights from metabolic and molecular markers - Moloney, Fiona (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2006)
Insulin resistance signifies an impaired biological response to insulin, and usually implies resistance to the effects of insulin on glucose uptake, metabolism, or storage. This defect is commonly observed in type 2 diabetes mellitus (T2DM) and the metabolic syndrome and is often found in association with other cardiovascular disease (CVD) risk factors including obesity, dyslipidaemia, hypertension and atherosclerosis. Altering the composition of fat in the diet can have a profound effect on insulin sensitivity whereby saturated fatty acids attenuate insulin sensitivity, while monounsaturated fatty acids can reverse this effect. The objective of this thesis was to examine the relationship between the n-6 polyunsaturated fatty acid conjugated linoleic acid (CLA) and insulin sensitivity, and its possible involvement in attenuating other risk factors associated with CVD. Several isoforms of CLA exist with cis-9, trans-11 CLA (c9, t11-CLA) which is the predominant dietary isoform and trans-10, cis-12 CLA (t10, c12-CLA) thought to have most biological activity.
Keywords: Molecular Medicine, Ph.D.; Ph.D. Trinity College Dublin